2014
DOI: 10.1093/inthealth/ihu090
|View full text |Cite
|
Sign up to set email alerts
|

Non-communicable disease training for public health workers in low- and middle-income countries: lessons learned from a pilot training in Tanzania

Abstract: The applied NCD epidemiology and control training piloted in Tanzania was well received and showed improvements in knowledge, skill and self-efficacy and changes in workplace behavior and institutional and organizational changes. Further evaluations are needed to better understand the impact of similar NCD trainings and future trainers should ensure that trainees have mentoring and workplace support prior to participating in an applied NCD training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…In Mozambique, after the implementation of a partnership program with the UK government, there was a significant improvement in the capacity of the healthcare workers for managing diabetes [ 42 ] and some studies have documented improvements in glucose control with patients living in areas where task shifting have been implemented [ 23 ]. A training program in Tanzania [ 63 ] successfully resulted in the elaboration of diabetes educational materials for patients, and a task shifting program with nurses in Kenya [ 64 ] showed nurses were capable of adhering to protocols and guidelines for diabetes care. An intervention in South Africa capacitating primary healthcare workers in identifying signs of diabetes and providing appropriate referral not only had an impact in this healthcare workers' knowledge but also improved early detection and referral for high risk, poorly controlled patients [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Mozambique, after the implementation of a partnership program with the UK government, there was a significant improvement in the capacity of the healthcare workers for managing diabetes [ 42 ] and some studies have documented improvements in glucose control with patients living in areas where task shifting have been implemented [ 23 ]. A training program in Tanzania [ 63 ] successfully resulted in the elaboration of diabetes educational materials for patients, and a task shifting program with nurses in Kenya [ 64 ] showed nurses were capable of adhering to protocols and guidelines for diabetes care. An intervention in South Africa capacitating primary healthcare workers in identifying signs of diabetes and providing appropriate referral not only had an impact in this healthcare workers' knowledge but also improved early detection and referral for high risk, poorly controlled patients [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in this systematic review had some limitations, as mentioned by their authors. These limitations include low number of participants [ 28 , 43 , 63 , 65 – 67 , 73 ], participants and centers not representative sample of the studied country [ 25 , 29 , 40 , 45 , 53 , 54 ]. Other studies reported high loss to follow-up [ 27 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies assessing the domains of self-efficacy or confidence were applied to strengthen leadership, managerial or teaching capacity [39][40][41][42]; working with patients [43][44][45][46]; and for the provision of care, such as treatment for non-communicable disease [47], anti-retroviral therapy [45], and providing mental health care [48][49][50][51], a topic which has become prevalent in more recent years.…”
Section: Objective 1: Domains Of Capacity Strengtheningmentioning
confidence: 99%
“…Wong dan Wong (2015) proves that most of the challenges in evaluation at this level 3 stage are due to internal and external factors. In addition, related to level 3 evaluation results, it needs external support such as u ' u , O u problems, the most commonly reported of self-motivated motivation in improving performance, and selfefficacy which is their belief in their ability to perform the tasks or actions necessary to achieve the outcome of the training in workplace (Davila,et al, 2015). It means that statement given by the trainee (participants) hence also obtained another conclusion that is related to the inherent elements from inside the employee which is personality character (internal) and supporting facility (external).…”
Section: Journal Of Educational and Learning Studiesmentioning
confidence: 99%